Competition/collaboration at the workplace - Gulis, Inna V.; Borisevich, Marina K. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The article founds the relevance of the study competition/collaboration at the workplace, given the definition, presents main directions of psychological investigations this phenomena. There are theoretical and methodological problems which make it difficult to carry out systematic studies of competition/ collaboration in organizations. The paper presents the attempt to classify competition/collaboration on different grounds and factors which influence on it manifestation and effectiveness of work. The results of investigation of competition/collaboration at the Belarusian workplace are presents.
Keywords: competition/collaboration at the workplace; behavioral strategy; factors; classification; activity; success of activities; dynamic processes; development